2008
DOI: 10.1007/s00280-008-0780-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted constitutive activation of signal transducer and activator of transcription 3 in human hepatocellular carcinoma cells by cucurbitacin B

Abstract: Our results suggest that cucurbitacin B may have a therapeutic value in suppressing the growth of human hepatocellular carcinoma. The mechanism may be attributable to the suppression of STAT3 phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 22 publications
4
69
3
Order By: Relevance
“…Cucurbitacin B, one of the most abundant forms of cucurbitacins, was found to effectively decrease the viability of HepG2 cells through apoptosis with a simultaneous decrease in the levels of the pro-apoptotic protein Bcl-2. Suppression of transcription factor signal transducer and activator of transcription-3 (STAT3) phosphorylation was associated with the cell killing effect of this natural compound [83] . Chan et al [84] were successful in achieving similar growth inhibitory effects of cucurbitacin B in Bel-7402 cells.…”
Section: Lupeolmentioning
confidence: 99%
See 3 more Smart Citations
“…Cucurbitacin B, one of the most abundant forms of cucurbitacins, was found to effectively decrease the viability of HepG2 cells through apoptosis with a simultaneous decrease in the levels of the pro-apoptotic protein Bcl-2. Suppression of transcription factor signal transducer and activator of transcription-3 (STAT3) phosphorylation was associated with the cell killing effect of this natural compound [83] . Chan et al [84] were successful in achieving similar growth inhibitory effects of cucurbitacin B in Bel-7402 cells.…”
Section: Lupeolmentioning
confidence: 99%
“…Zhang et al [83] showed the decrease in tumor volume along with tumor growth inhibition exerted by cucurbitacin B in mice xenografted with HepG2 cells, whereas Chan et al [84] demonstrated the inhibitory activity of cucurbitacin B on the growth of xenografted BEL-7402 tumor. Nevertheless, the in vivo mechanisms of such antitumor effects of cucurbitacin B were not studied.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Jayaprakasam and co-workers demonstrated the cytotoxic properties of cucurbitacins B, D, E and I, isolated from the fruits of Cucurbita andreana, against colon, breast, lung and central nervous system cancer cell lines (Jayaprakasam et al, 2003). Among this class of compounds, cucurbitacin B is the most studied, and while several studies demonstrated its efficacy in different models of cancer, including in vivo tumor xenografts (Liu et al, 2008;Wakimoto et al, 2008;Zhang et al, 2009;Chan et al, 2010), there is disagreement regarding the mechanisms underlying its anticancer activity. Suppression of the oncogene STAT 3 (signal transducer and activator of transcription 3) appears to be related to tumor inhibition (Zhang et al, 2004;Chan et al, 2010b), which does not exclude alternative mechanisms (Yasuda et al, 2010).…”
Section: Research Articlementioning
confidence: 99%